The Sustainability of Community Development in Area Pig Farming withSerasah System Based on Spiritual and Cultural Aspec - Pangerungan, Yans (2015)
The aim of this research is to evaluate the sustainability of pig farming with serasah system based on spiritual and cultural aspects in Kertek region, Wonosobo regency. The research was performed at six villages located in Kertek region, i.e : Candimulyo, Candiyasan, Kapencar, Pagerejo, Purbosono and Reco, with three steps activities : preparation, data collection and data analysis. The preparation step consists of collecting information from literature review required for starting this research. Data collection was conducted to gain primary data which is related to pig farming with serasah system by observation method, in depth interview and questioner survey to identify factors that having role on pig farming sustainability with serasah system. In depth interview is started by interviewing some informants of pig farmers which have farming with serasah system. The next step is analyzed each aspect from the obtained data. The result of sustainability of spiritual and cultural aspects showed that the application of sustainability concept is a good method because inheritanced by their ancestors. It has been well done by their descendant and the spiritual of farmer is still strong. Therefore, the farmer belief toward their religion did not lose as well.